Curative effect of vitamin C and brassinolide on growth of mungbean (Vigna radiata (L.)Wilczek) under salinity stress (Journal of the College of Basic Education, 2022)
A field experiment was carried out during 2018growing season, to investigate the influence of foliar application of vitamin C at concentration of 0, 60 and 120mg.l-1 in addition to brassinolide 0,2 and 4mg.l-1 on vegetative growth parameters of mungbean plants subjected to salt stress (NaCl) at four levels (0.9,5.5,10and15dS.m-1). The experiment was conducted in factorial Randomized Completely Block Design (R.C.B.D) with three replicates and means were compared at Least Significant Difference (LSD) at probability of 0.05. Results indicated that salt stress levels from0.9 to15dS.m-1 reduced significantly the average of vegetative growth parameters (plant height, leaf area, dry weight and chlorophyll content). Moreover, application of vitamin C and brassinolide increased significantly the average of vegetative growth parameters above, and had reduced the adverse effect of salt stress particularly 120 mg.l-1 vitamin C and 4mg.l-1 brassinolide.